Konsep Ketubuhan dalam Asmara Berdarah Ken Arok Ken Dedes: Kajian Feminisme Simone De Beauvoir - Jalu Norva Illa Putra (Stilistika : Journal of Indonesian Language and Literature, 2021)
The discussion about feminism never ceases to be debated in all aspects. Women and men are always contested about who is "the most". This paper looks at this aspect more fundamentally through a novel entitled Bloody Asmara Ken Arok Ken Dedes. The concept of the body in this work is useful for establishing a legitimacy for power and recognition. Until in the end this body discourse was overturned by the resistance about body ownership. Ken dedes won to be a subject that is able to stand alone and even become a domineering person.